(untitled) (Journal of Asian Development Studies, 2025)
Sustainable consumption behaviour can address environmental, social, and economic problems created by unsustainable consumption behaviour, whereas socio-economic factors are crucial factors which influence human consumption behaviour. Therefore, this study conducted a comparative analysis of urban-rural Khyber Pakhtunkhwa regarding the effects of socio-economic factors on sustainable consumption behaviour. The Krejcie and Morgan method was used to determine the sample size, and the multistage cluster sampling technique was used to form the whole sample from the target population. Data from sampled respondents were collected through self-administered questionnaires. Partial Least Squares Multigroup Analysis (PLS-MA) was used to analyse the data. The findings of this study demonstrate that all socio-economic factors included in this study, except Gender, significantly affect sustainable consumption behavior. The coefficients of Gender (β=0.15, P<0.05), education (β=0.44, P<0.05), and income (β=0.35, P<0.05) are positive and statistically significant, which means these variables have positive effects on sustainable consumption behaviour. The coefficient of Gender (β= 0.08, P= 0.43) is positive; however, it is statistically insignificant. The coefficient of employment status (β=-0.22, P <0.05) is negative, which implies that employed people are more sustainable than unemployed people. The results further show that the effects of socioeconomic factors on sustainable consumption behaviour are more potent in urban areas than in rural areas. Finally, the study presents some valuable recommendations for policymakers and businesses.